Preparation and (Li+) Conductivity of Highly Deproteinized Natural Rubber Having Epoxy Group - Klinklai, Warunee (Frontiers in Engineering Innovation Research, 2005)
Highly deproteinized natural rubber having epoxy group (LENR) was applied to transport Li* as an ionic conducting medium. LENR was prepared by epoxidation of deproteinized natural rubber followed by oxidative degradation with (NH4)2S2O8 and propanol. The resulting liquid rubber (Mn = 104) was found to have well defined terminal groups,i.e. aldehyde group and α-β unsaturated carbonyI group, which is useful for further chemical modification, without loss of epoxy group. The glass transition temperature (Tg) and gel content of natural rubber increased after epoxidation whereas they decreased after degradation. LENR was confirmed to have a potential application as an ionic conducting medium due to high polarity and mobility, necessary for a solid polymer electrolyte.